(3GdJNWjW GdJQHhj hGdJfejI (B/s - (3LhgQ, Ydj UGdMs ((3GdEScfOQjI(B: s (3GdecJHI GdYUQjI ddfTQ hGdJhRjY(B, s, 2009)
(3jVe GdJNWjW GdJQHhj hJWhQ acQJg, GdJNWjW GdJQHhj aj eUQ, GdJNWjW GdJQHhj hGdJfejI GdGbJUGOjI aj eUQ, GdJNWjW dRjGOI GdYGFO GdGbJUGOj aj GdJYdje, GdJNWjW dJbdjd cdaI GdJYdje HGdeDSSGJ GdJYdjejI, GdJNWjW dehGLgI eTcdI GSJfRGa GdYbhd GdYQHjI, GdJNWjW dGSJKeGQ GdWGbGJ GdHTQjI aj GdbQf GdMGOj hGdYTQjfs
(3GdeQGLY U(B.220s
Keywords: (3GdJNWjW GdJQHhjs; (3GdJfejIs; (3GdJfejI GdEbJUGOjIs; (3eUQ(B- (3GdJNWjW GdJQHhjs